Internal CSR and blue-collar workers' attitudes and behaviors in China: a combination of a cross-sectional study and a field experiment - Nick Lin-Hi; Xiaohan Gao-Urhahn; Torsten Biemann; Irmela F. Koch-Bayram (Asian Business & Management, 2022)
While a positive relationship between corporate social responsibility (CSR) and employee outcomes has been widely researched, most studies have been conducted in a Western context and for white-collar employees. Thus, little is known about Chinese blue-collar workers' reactions to CSR. In two studies, we investigated the outcomes of internal CSR for blue-collar workers in the Chinese manufacturing industry. In the cross-sectional study, we found that perceived internal CSR is positively related to job satisfaction, trust in management, and perceived supervisory support. To further disentangle cause-and-effect relationships, we conducted a field experiment. The results show that internal CSR information increases performance quantity and lowers complaints, but also lowers performance quality and does not affect workers' voice behavior. Our results further reveal that workers' attitudes toward ethics and social responsibility are an important moderator which strengthens some of the hypothesized effects.
Keywords: M12; M14; 650; Blue-collar workers; China; Internal CSR; Person-organization fit; Social exchange; Work-related attitudes and behaviors